Método AHP no auxílio à tomada de decisão de alternativas mediante problemas no fluxo de manutenção de respiradores. - Bergamini, Marco Bruno Moretto [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
When assessing problems that involve decision-making process, these are constantly present in any context, and usually involve more than one relevant criterion in the choice. Thus, due to the complexity of this process, the decision maker often intends to include both qualitative (opinions) and quantitative (data) criteria. This research uses the multicriteria decision method, based on a multinational automobile company, which had a problem with bottlenecks in the respirator maintenance flow. Thus, the objective was to evaluate the results that would be obtained with the application of the Analytic Hierarchy Process (AHP) method with the BOCR model (Benefits, Opportunities, Costs and Risks) for the prioritization and selection of equipment, based on its components, within this maintenance flow, in the pandemic COVID19. This research is of an applied nature, qualitative approach, descriptive objective and the research method is Case Study/Mathematical Modeling. After applying the method, the best alternative was obtained, according to the criteria considered relevant and compared with the actual results obtained by the company

Avaliando-se problemas que envolvem o processo de tomada de decisão, estes, estão constantemente presentes em qualquer contexto, e costumeiramente envolvem mais de um critério relevante na escolha. Desse modo, pela complexidade desse processo, o tomador de decisão muita das vezes pretende incluir tantos critérios qualitativos (opiniões), como quantitativos (dados). Assim, essa pesquisa utilizou o método de decisão multicritério, com base em uma empresa automobilística multinacional, com problemas de gargalos no processo de manutenção dos respiradores. Com isso, o objetivo foi avaliar os ganhos que seriam obtidos com a aplicação do método Analytic Hierarchy Process (AHP) combinado ao modelo BOCR (Benefícios, Oportunidades, Custos e Riscos) para a priorização e seleção de equipamentos, com base em seus componentes, dentro desse fluxo de manutenção, na pandemia COVID-19. Esta pesquisa é de natureza aplicada, abordagem qualitativa, objetivo descritivo e o método de pesquisa é Estudo de Caso/modelagem matemática. Após a aplicação do método, foi obtida a melhor alternativa, de acordo com os critérios considerados relevantes e comparar aos resultados reais obtidos pela empresa.
AHP method in aiding the decision making of alternatives through problems in the ventilators maintenance flow.
Keywords: Multicriteria Decision; pandemic; AHP; BOCR; Decisão multicritério; COVID-19; respiradores; pandemia; Processo decisório por critérios múltiplos; Respiradores (Equipamentos médicos); Insuficiência respiratória